2023
DOI: 10.3390/ijms24098297
|View full text |Cite
|
Sign up to set email alerts
|

ROS Consumers or Producers? Interpreting Transcriptomic Data by AlphaFold Modeling Provides Insights into Class III Peroxidase Functions in Response to Biotic and Abiotic Stresses

Abstract: Participating in both biotic and abiotic stress responses, plant-specific class III peroxidases (PERs) show promise as candidates for crop improvement. The multigenic PER family is known to take part in diverse functions, such as lignin formation and defense against pathogens. Traditionally linked to hydrogen peroxide (H2O2) consumption, PERs can also produce reactive oxygen species (ROS), essential in tissue development, pathogen defense and stress signaling. The amino acid sequences of both orthologues and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Nonetheless, recent studies have pointed out that sets of amino acid residues, mostly at or close to the enzyme active site, have been positively selected for and thus might be useful in function prediction (Ren et al 2014; Kupriyanova et al 2015; New et al 2023). The present study also showed phylogenetic clustering of PRX genes from different taxa, and this could be used to predict functional similarity among the genes.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, recent studies have pointed out that sets of amino acid residues, mostly at or close to the enzyme active site, have been positively selected for and thus might be useful in function prediction (Ren et al 2014; Kupriyanova et al 2015; New et al 2023). The present study also showed phylogenetic clustering of PRX genes from different taxa, and this could be used to predict functional similarity among the genes.…”
Section: Discussionmentioning
confidence: 99%